Sosialisasi pemahaman kebencanaan di Kelurahan Pasie Nan Tigo, Kecamatan Koto Tangah, Kota Padang - Nefilinda Nefilinda; Slamet Rianto; Jamsari Jamsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The position of Pasie Nan Tigo Village on the Coast of Sumatra causes the area to be very risky to coastal abrasion, floods, earthquakes, and even by tsunamis. Therefore, the PKM activities undertaken are aimed at increasing the understanding and readiness of the community in the village in dealing with disasters so that the impact of disasters can be reduced. The activity was carried out using the lecture/counseling method followed by a discussion. The results of the activities showed that in general the community was well-informed in facing disasters. Understanding of natural phenomena especially related to the impact of the earthquake and tsunami such as: the receding of sea water, cracked houses, sudden emergence of water sources, strong and repeated earthquakes and the running of animals towards the land to be a sign of what they should do. The decision to be prepared to evacuate is generally depending on the information released by the government. The community is also equipped with saving valuable family documents such as diplomas, certificates, ID-Card, family card, etc. by doing digital scanning and backing up. Photos and results are stored in a cloud system in the form of an email or in the google drive facility. Communities are also taught about making disaster signs and making agreements especially in families to determine safe gathering places by using the shortest evacuation route map or buildings that can function as shelters.